The creation process in digital art - Marcos, Adérito (2020)
The process behind the act of the art creation or the creation process has been the subject of much debate and research during the last fifty years at least, even thinking art and beauty has been a subject of analysis already by the ancient Greeks such were Plato or Aristotle. Even though intuitively it is a simple phenomenon, creativity or the human ability to generate innovation (new ideas, concepts, etc.) is in fact quite complex. It has been studied from the perspectives of behavioral and social psychology, cognitive science, artificial intelligence, philosophy, history, design research, digital art, and computational aesthetics, among others. In spite of many years of discussion and research there is no single, authoritative perspective or definition of creativity, i.e., there is no standardized measurement technique. Regarding the development process that supports the intellectual act of creation it is usually described as a procedure where the artist experiments the medium, explores it with one or more techniques, changing shapes, forms, appearances, where beyond time and space, he/she seeks his/her way out to a clearing, i.e., envisages a path from intention to realization. Duchamp in his lecture “The Creative Act” states the artist is never alone with his/her artwork; there is always the spectator that later on will react critically to the work of art. If the artist succeeds in transmitting his/her intentions in terms of a message, emotion or feeling to the spectator then a form of aesthetic osmosis actually takes place through the inert matter (the medium) that enabled this communication or interaction phenomenon to occur. The role of the spectator may become gradually more active by interacting with the artwork itself possibly changing or becoming a part of it [2][4].